Effects of cotton straw added to total mixed pelleted feed on the composition of rumen microbiota in breeding ewes - Zhijun Zhang; Zhijun Zhang; Duanji Sang; Duanji Sang; Junyu Zhang; Junyu Zhang; Lingling Su; Lingling Su; Amat Guzalnur; Amat Guzalnur; Liangzhong Hou; Liangzhong Hou; et al. (Frontiers in Microbiology)
This study aimed to investigate the effects of adding increasing amounts of cotton straw to the feed of breeding ewes on the bacterial and fungal microbiota of the rumen. A single-factor, completely randomized design was adopted, in which 120 ewes of small-tailed Han sheep were randomly divided into six groups, 20 ewes per group. Control group 1 (CK1) was fed a diet without cotton straw, while control group 2 (CK2) contained cottonseed meal in place of cotton straw. The experimental groups were supplemented with 20% (M20 group), 30% (M30 group), 40% (M40 group), or 50% (M50 group) cotton straw. The trial included a 30-day pre-trial period and a 270-day formal trial period. The results showed that, among the rumen bacterial microbiota, there was no significant difference in the number of operational taxonomic units (OTUs) between the groups. The ACE and Chao biodiversity indices of the CK2 group and M20-M50 groups were significantly lower than those of the CK1 group. Principle coordinate analysis (PCoA) of bacterial diversity revealed clear separation between the CK2 group and the M20-M50 groups compared with the CK1 group. With respect to rumen fungal microbiota, the M20 and M50 groups had the highest number of unique OTUs. There were no significant differences in abundance and diversity indices, and PCoA showed no obvious clustering differences among the groups. In summary, supplementing the basal diet with different proportions of cotton straw reduced the diversity of rumen bacteria and altered the composition of rumen bacterial and fungal communities. Adding more than 40% cotton straw significantly increased the abundance of Proteobacteria, which could have adverse effects on sheep growth performance.